Neutron-Driven Nucleosynthesis in Stellar Plasma - Spartà, R.; La Cognata, M.; Guardo, G. L.; Palmerini, S.; Sergi, M. L.; D’Agata, G.; Lamia, L.; Lattuada, D.; Oliva, A. A.; Pizzone, R. G.; Rapisarda, G. G.; Romano, S.; et al. (Frontiers in Physics, 2022)
A large uncertainty for the slow neutron capture nucleosynthesis (s-process) models is caused by the amount of neutrons available to the process itself. This quantity is strongly affected by the 13C(α,n)16O, and 22Ne(α,n)25Mg reaction cross sections, whose measurements at energies corresponding to the s-process thermal conditions (∼102 keV) are mainly hampered by the Coulomb barrier. For this reason, indirect approaches could offer a complementary way of investigation and, among these, the Trojan Horse Method (THM) has been applied to determine these cross sections overcoming the Coulomb barrier. With this approach, a low-energy binary reaction cross section can be obtained selecting the quasi-free contribution from a suitable three-body reaction cross section, taking advantage of the cluster structure of proper nuclei.